TruCluster server handbook - Fafrak, Scott. (Digital Press, 2003)
The TruCluster Server Handbook authoritatively details how to plan, design, install, configure, and administer a cluster of Tru64 UNIX systems. The book explains how to configure and optimize hardware underlying a TruCluster server, including storage servers so critical to running a high-end cluster operation. This book provides best practices and techniques drawn from the authors' extensive experiences in the field with systems designers, systems managers, developers, and users. The authors include a former Tru64 UNIX Technical Group Leader with HP's Consulting Division and a top industry figure, and two former TruCluster Server Team Leaders with the Customer Support Center. Learn to install TruCluster Server from the ground up Get the most out of your cluster environment with the authors' practical tips and tricks Attain availability, scalability, and simplified manageability in your IT systems operation.